The Neoproterozoic-lower Paleozoic sequence of the Sierra de Mojotoro, Eastern Cordillera: Sedimentary provenance (Sr–Nd, U–Pb, and clay mineralogy) and its tectonic implications for western Gondwana. (December 2020) - Aparicio González, Pamela A.; Hauser, Natalia; de Oliveira Carvalho, Manuela; de Morisson Valeriano, Claudio; Eric Cayo, Lubín; Barrientos, Andrea; Impiccini, Agnes; Reimold, Wolf Uwe; Heilbron, Mónica; Pimentel, Márcio M.
Abstract: Comparative analysis of mineralogy and post-depositional thermal evolution, as well as Sr–Nd and U–Pb on zircon isotope analysis of metapelites/pelites and sandstones of the Neoproterozoic to Paleozoic succession (Puncoviscana Complex, Mesón and Santa Victoria groups) in the Sierra de Mojotoro of northwestern Argentina has been conducted. Samples are mainly composed of different phyllosilicate minerals: illite, chlorite, kaolinite, illite/chlorite, corrensite, and K-bentonite. Some could have been incorporated through an inheritance process, whereas others probably originate from the alteration of volcanic precursor minerals (from Pampean and Famatinian magmatism). The Nd–Sr fingerprints for the Eastern Cordillera and the Puna are defined. For the Eastern Cordillera Epsilon Nd is more negative, the Nd model age is a little older (until 1.7 Ga), and these rocks show more radiogenic 87 Sr/ 86 Sr ratios when compared with Puna rocks. Nd isotopes and U–Pb ages on zircon suggest that the sedimentary rocks of the Eastern Cordillera were formed during the Paleozoic from reworking of continental crust. The detrital zircon data for samples from the Santa Victoria Group (Floresta, San Bernardo and Mojotoro formations) show a main population of lower-middle Cambrian age, and only one contemporaneous zircon grain of volcanic origin yielded a Floian age (473 Ma). The new data, when compared with previous data from the Puna and other parts of the Eastern Cordillera, allow us to delineate a model for the Neoproterozoic to lower Paleozoic evolution of NW Argentina that involves the evolution from an active margin. Highlights: We report U–Pb, Sr–Nd and clay mineralogy of Paleozoic rocks of the Eastern Cordillera. Paleo-to Mesoproterozoic TDM ages suggest unroofing of continental crust. The Santa Victoria Group, show a main provenance of Cambrian on zircon age. The lower Paleozoic sequences of NW Argentina indicate an active margin.